The Effect of Mastering the Al Miftah Lil Ulum Method on Improving the Comprehension Structures Students Madrasah Aliyah Amanatulloh - Miftahuddin Mustaqim; Mahbub; Zohaib Hassan Sain (Universitas Islam Negeri Palopo, 2026)
This study aims to examine the effect of mastery of the Al-Miftah Lil Ulum method on improving fahmut al-tarakib (understanding of Arabic sentence structure) among 11th grade MIPA students at Madrasah Aliyah Amanatulloh for the 2025/2026 academic year. This study employed a numerical-analytic framework utilizing a single-predictor modeling structure, with data drawn from a cohort of thirty learners selected through criterion-based inclusion. Data collection was conducted through a Likert questionnaire for the independent variable (mastery of the method), pre-post tests for the dependent variable (fahmut al-tarakib), and supporting documentation, which was then analyzed using SPSS 26. The Kolmogorov-Smirnov normality test indicated a normal residual distribution (Asymp. Sig. = 0.192 > 0.05). The F test confirmed the significance of the regression model simultaneously (F = 16.979; Sig. = 0.000), while the t test proved a positive and significant partial effect (t= 4.121; Sig. = 0.000; β = 0.614). Pre-test scores (range 55-78) and post-test scores (68-92) showed a stable average increase of 12-14 points across all respondents. The novelty of this study lies in its empirical validation of a traditionally pesantren-based nahwu method through a modern quantitative regression approach within a science-track Madrasah Aliyah context, thereby positioning the Al-Miftah Lil Ulum method as a data-driven and digitally adaptive Arabic grammar learning innovation rather than a purely classical instructional practice. The research findings confirm the effect of the Al-Miftah Lil Ulum method as an adaptive Arabic grammar learning innovation in the digital age. This study provides empirical curriculum recommendations for senior high schools to address students' Arabic syntactic difficulties, while enriching the evidence base for the development of Islamic language competencies.